Financial Management Quality on Aluminium Furniture Business - Jariah, Ainun; Lukiana, Ninik; Hartono, Hartono; Irwanto, Jesi (IMPOWERMENT SOCIETY, 2022)
The wooden household furniture now does not guarantee to last long, because the poor quality of woods material. Many alternative choices other than woods, one of which is aluminum. The aluminum furniture business has penetrated rural areas. The partner target are aluminum business owners in Biting Village. Their previous business is to fulfill the manufacture of trellises, fences and household furniture based on orders. The weakness of partner mainly lies in: (1) the limited human resources ability in manage their business; (2) the inability of human resources who understand business bookkeeping regularly; (3) unseparated business and household finances and; (4) limited capital access. This activity is expected to give results according to the targets: (1) increase partner skills in running its business sustainably; (2) strengthening the ability of partners in the preparation of bookkeeping regularly and correctly; (3) increasing the ability of partners in separating business and household finances and; (4) obtaining easy capital access.